LANDSCAPE INTERVENTION DESIGN STRATEGY WITH APPLICATION OF ISLAMIC ORNAMENTATION AT TRUNOJOYO PARK MALANG, JAWA TIMUR, INDONESIA - Samudro, Harida (Journal of Islamic Architecture, 2020)
Trunojoyo Park in Malang City is one of the city parks that has a predicate as the best park. The government of Malang city supports this park into a city park that must be visited by the tourists. The problem is trunojoyo park requires a direction of future development by looking at the perception of visitors who visit the park. The purpose of this study is to know the direction of the new design to find the appropriate design criteria in relation to one's response from the perceptions seen. The architectural intervention in the landscape is one way of approaching how to view the perception in the realm of architectural design. In two ways: temporary intervention and permanent intervention, this method looks at how one's response perceives the architectural element as an aesthetic element in which there is an Islamic ornament as one of the objects applied. This study used descriptive research through field observations by giving random questionnaires that were divided into men and women. Analysis and discussion are done by sorting and calculating each variable of choice of the respondent quantitative). They were further evaluated to determine the factors of visitor perception assessment of aesthetics Park City. This study shows that the order and diversity of vegetation, completeness of facilities, security, and comfort of the Park City are the factors of assessment of visitors to the aesthetics of the Park City. This research has benefited from the emergence of new theories regarding the visitor's assessment of the aesthetic City Park.Â